2016
DOI: 10.30703/cije.321384
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing Activity Plans’ Parental Involvement Section in Early Childhood Education

Abstract: developments and learning achievements of the children. Study indicated that not only quality of the parental involvement in activity plans should be supported, but also quantity of them.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 3 publications
0
5
0
1
Order By: Relevance
“…For this reason, it is important for PPE schools in Zanzibar to focus on the practice side by involving parents in educational matters for more experiences in learning of their children. Kurtulmus (2016) revealed out that schools have hard time reaching parents and capturing their attentions. Also, parents have limited time knowing how to get involved in the learning of their children.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For this reason, it is important for PPE schools in Zanzibar to focus on the practice side by involving parents in educational matters for more experiences in learning of their children. Kurtulmus (2016) revealed out that schools have hard time reaching parents and capturing their attentions. Also, parents have limited time knowing how to get involved in the learning of their children.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, parental involvement has positive impact on children leaning. Researches indicate increased of academic achievements with children whose parents get involved in the education of their children including staying longer in school, get more engaged in school works , attend school regularly, have better social skills, show improved behavior and adapt well to school (Epstein, 2002, Ekinci-Vural & Dogan-Altun , 2021& Kurtulmus, 2016.…”
Section: Introductionmentioning
confidence: 99%
“…Parental involvement in child's education has been accepted as a crucial element. Studies on parental involvement do not only prove their positive effect on child's development, but also present specific links among the structure of the involvement and children's academic achievement and social emotional outcomes (Kurtulmuş, 2016). Home-school relationship refers to the formal and informal connections between parents and their young children's educational settings.…”
Section: Discussionmentioning
confidence: 99%
“…Studies showed that parental involvement is one of the key factors affecting children's reading performance (Kurtulmuş, 2016;Gilleece, 2015;Peissig, 2002).…”
Section: Methodsmentioning
confidence: 99%
“…Ev temelli aile katılımı; ev ortamını çocuklara uygun hale getirmek, öğretmenin önerdiği etkinlikleri evde uygulamanın yanı sıra ebeveynlerin ev ödevlerine yardım etmesi, gününün nasıl geçtiğini sorması, kitap okuması, oyun oynamasını da içermektedir. Okul temelli aile katılımı; ailelerin sınıf içindeki etkinliklere katılması, veli toplantılarını takip etmesini içerirken okul-aile işbirliği temelli katılım;anne babalar ve öğretmenlerin iletişim halinde olmalarını içermektedir (Özel,Çağdaş ve Konca, 2016;Erkan, Uludağ ve Dereli, 2016; Günay Bilaloğlu ve Aktaş Arnas, 2019; Kurtulmuş, 2016). Yapılan pek çok araştırmada aile ve okulu ortak paydada buluşturan modellerin hem çocukların başarısını hem de ailelerin bilgi ve becerilerini arttığı ortaya çıkmıştır (Tezel Şahin ve Özyürek, 2016).…”
unclassified